Access, Community Capacity, and Socio-Economic Impacts on the Implementation of Social Forestry Programs in the Perum Perhutani KPH Telawa Working Area - Adhi, Esa Jati Manunggal Sukma; Utami, Trisni (Masyarakat: Jurnal Sosiologi, 2025)
Despite increasing interest in social forestry, limited research has explored the interplay between community capacity and access within Indonesia’s Social Forestry Utilization Permit (IPHPS) scheme. This study examines the relationship between community capacity, access, and socio-economic impacts to inform effective policy implementation. Employing a qualitative case study approach, it focuses on a community granted an IPHPS Decree within the Perum Perhutani Forest Management Unit (KPH) Telawa. The findings identify three key dimensions of community capacity: technical capacity (local knowledge and skills), networking capacity (social capital and relationships), and cultural capacity (local wisdom and practices). While legal access to forest permits is necessary, achieving the program’s socio-economic objectives also requires enhanced access to financial capital, technical assistance, government engagement, and private sector partnerships. Strengthening these capacities is critical to ensure the transformative potential of social forestry is fully realized for community welfare and sustainable forest governance.